Talent Relationship Management Competitive Recruiting Strategies in Times of Talent Shortage - Trost, Armin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
In times of growing talent shortage, companies have to find new ways to fill their strategic positions from the outside. This book presents useful and competitive solutions for hiring talented and motivated employees. The author presents four concrete fields of action to achieve this and provides the reader with definitions of strategically relevant key and bottleneck functions. The book emphasizes the fact that employers must sell relevant functions just like they would as part of an employer branding strategy. Employers are moving towards active sourcing strategies beyond job ads and headhunting. They must maintain and manage relations with promising talent once they have been identified. Finally, employers must ensure a positive candidate experience. This book serves as a handy reference for HR managers and talent recruiters.
Introduction -- The Labour Market of the Future -- An Overview of Talent Relationship Management -- Defining Relevant Target Groups -- The Employee Value Proposition -- Active Sourcing Strategies -- Candidate Retention -- The Positive Candidate Experience -- Framework Conditions -- Conclusion.
Keywords: Business; Public relations; Leadership; Personnel management; Success in business; Careers; Economics; Business and Management; Human Resource Management; Popular Science in Economics / Management; Careers in Business and Mangagement; Corporate Communication/Public Relations; Business Strategy/Leadership.; Electronic books